Indonesian Wood as Material for Acoustic Guitars and Violins - Indraswari Kusumaningtyas; Subagio Subagio (Wood Research Journal, 2012)
Traditionally, acoustic guitars and violins are made from European woods. Spruce is most preferred for the top plate (soundboard), whereas maple, sycamore and rosewood are often used for the back plate. However, these woods are not easily available in Indonesia. In this paper, we present a study on the suitability of a selection of Indonesian woods, namely acacia, mahogany, pine, sengon and sonokembang, as materials for acoustic guitars and violins. The most important acoustical properties for selecting materials for musical instruments, i.e. the speed of sound, the sound radiation coefficient and the damping factor, were investigated. Furthermore, the performance of pine and mahogany were tested by making them into a violin and a guitar. The vibration frequency spectrum and the damping factor of the top plate were measured. The results show that the acoustical characteristics of mahogany are very close to those of maple and still quite close to those of Indian rosewood, which makes it a very suitable local material for back plates. Pine has quite similar acoustical characteristics to spruce. Although its sound radiation coefficient is slightly lower, its aesthetic appeal and workability makes pine a suitable alternative for top plates. However, instruments with pine top plates exhibit different tonal colour compared to instruments with spruce top plates, due to some differences in the vibration frequency spectrum. Furthermore, the generally higher damping factors of pine and mahogany compared to those of the European woods should be taken into account, because they affect the sustain-time of the generated sound.